From Fiqh al-Ibadat to Muamalat: Repositioning Zakat Management in Indonesia in the Perspective of Maqāṣid Al-Sharī’ah - Fakhruddin, Fakhruddin; Hasan, Sudirman; Firdaus, Dwi Hidayatul; Hidayat, Hakmi (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
Zakat is one of the pillars of Islam and is considered an instrument that can potentially contribute to the economic development of the Muslim community in Indonesia. However, the current system and management of zakat have not been able to minimize the gap between the potential zakat that exists and the actual zakat that can be collected. This paper aims to examine zakat in its position as fiqh al-ibadat (Islamic jurisprudence of worship) and the consequences of its limited application, if not non-existent. Therefore, the purpose of this paper is to complement existing literature by proposing a new solution to the problem of zakat. This empirical legal study employed the maqāṣid al-sharī’ah (objectives of Islamic law) approach. Data were collected by means of interview and literature review from relevant journal articles, books, and websites. The results of the study revealed that there is a need to reposition zakat from fiqh al-ibadat to fiqh muamalat. This will allow for more flexible zakat management that will have a maximum impact on the welfare of the Muslim community. Therefore, it can be argued that from the perspective of maqāṣid al-sharī’ah, zakat is not only an act of worship related to the purification of wealth, but more than that, zakat can also be an instrument to promote the welfare and economic development of society if it is managed effectively and properly. The change in meaning and paradigm is significant to ensure that the maqāṣid al-sharī’ah can be achieved effectively.